Birth Cohort Consortium of Asia: Current and Future Perspectives. (October 2017) - Kishi, Reiko; Zhang, Jun Jim; Ha, Eun-Hee; Chen, Pau-Chung; Tian, Ying; Xia, Yankai; Tsuchiya, Kenji J.; Nakai, Kunihiko; Kim, Sungkyoon; Hong, Soo-Jong; Hong, Yun-Chul; Lee, Jeong-Rim; et al.
Abstract : Background: The environmental health of children is one of the great global health concerns. Exposures in utero and throughout development can have major consequences on later health. However, environmental risks or disease burdens vary from region to region. Birth cohort studies are ideal for investigating different environmental risks. Methods: The principal investigators of three birth cohorts in Asia including the Taiwan Birth Panel Study (TBPS), the Mothers and Children's Environmental Health Study (MOCEH), and the Hokkaido Study on Environment and Children' Health (Hokkaido Study) coestablished the Birth Cohort Consortium of Asia (BiCCA) in 2011. Through a series of five PI meetings, the enrolment criteria, aim of the consortium, and a first-phase inventory were confirmed. Results: To date, 23 birth cohorts have been established in 10 Asian countries, consisting of approximately 70, 000 study subjects in the BiCCA. This article provides the study framework, environmental exposure and health outcome assessments, as well as maternal and infant characteristics of the participating cohorts. Conclusions: The BiCCA provides a unique and reliable source of birth cohort information in Asian countries. Further scientific cooperation is ongoing to identify specific regional environmental threats and improve the health of children in Asia. Abstract : Supplemental Digital Content is available in the text.